Financial knowledge, attitude and behaviour of young working adults in Malaysia - Yong, Chen Chen; Yew, Siew Yong; Wee, Chu Kok (Faculty of Economics and Administration, University of Malaya, 2018)
A conceptual model was proposed based on the theory of planned behaviour to examine the relationship between financial knowledge, attitude, behaviour and financial literacy among young working adults in Malaysia. Perceiving financial literacy as a developmental process which includes knowledge and application dimensions, the proposed model was tested on a sample of 1915 young working adults from Klang Valley, Malaysia. Data was analysed using structural equation modelling (SEM). Results indicated financial education positively influenced financial knowledge which in turn, significantly predicted both financial attitude and behaviour. Attitude partially mediated the effect of knowledge on behaviour. Analysis revealed that in terms of financial attitude, “future and non-impulsiveness” was significant while in financial behaviour, “expenditure monitoring and saving behaviour” was critical. In terms of ethnic background, the Chinese possessed the highest financial knowledge and behaviour while Indians possessed the highest financial attitude. No gender difference was noted on any relationships. Initiatives and interventions on making financial education accessible as well as gradual change of attitude are recommended for immediate actions.